ANALYSIS OF ENGLISH LEARNING STRATEGIES AT NURUL JADID ISLAMIC BOARDING SCHOOL PROBOLINGGO - Faruq, Abdul Qudus Al; Zahro, Siti Fatimatus (International Journal of English Learning and Applied Linguistics (IJELAL), 2024)
The public assumption that Salafiyyah Islamic boarding schools focus solely on classical texts (kitab kuning) and Arabic is contrasted by Nurul Jadid Islamic Boarding School, which combines both Salafiyyah and modern educational systems. Notably, Nurul Jadid has implemented foreign language learning strategies, including English, through an institution called FLDI. Based on this background, the research aims to analyze English language teaching strategies at FLDI, one of Nurul Jadid's language institutions. This study employs a qualitative approach, gathering data through interviews, observations, and documentation, as well as relevant literature sources from websites and other references. The findings reveal that FLDI is an effective language institution within Nurul Jadid, successfully applying systematic and conducive English teaching strategies. Programs are structured daily, weekly, monthly, and annually, supported by a language-friendly environment, including Monolingual Areas, Word Walls, and the Judgment program. These programs and supporting environments reflect FLDI's innovative and structured approach to managing English learning dynamics.